An assessment of correlations of forced convection heat transfer to water at supercritical pressure. (February 2015) - Chen, Weiwei; Fang, Xiande; Xu, Yu; Su, Xianghui
Highlights: Evaluates 26 correlations of heat transfer to supercritical water. Compiles 3220 experimental data points for the evaluation. Evaluates based on both entire database and three heat transfer regimes. Provides a guide to choosing the best correlation for engineering design. Abstract: The heat transfer of supercritical water is essential for supercritical water-cooled nuclear reactors. Many empirical correlations for heat transfer to supercritical water were proposed over the past few decades. Some evaluations of the correlations were conducted, and inconsistent conclusions appeared owing to limited correlations or experimental data. This work presents an extensive survey of the literature of correlations and experiments of forced convection heat transfer to water flowing upward in vertical tubes at supercritical pressure. There are 26 correlations found, and an experimental database containing 3220 data points from vertical tubes are compiled from nine independent laboratories. All available correlations are assessed against the experimental database. The results show that the best correlation has a mean absolute deviation of 12.8%, predicting 82.3% of the database within ±20%. The entire database is divided into three categories, and the correlations which can give the most accurate predictions of the experimental data from different categories are also identified. The results provide a guide to choosing a proper correlation for engineering practice. Some topics worthy of attention for future studies are indicated.